Propuesta algorítmica para el ocultamiento de fotografías usando criptografía y esteganografía - López Egúsquiza, Charl Jóhanson (2013)
In this work, we propose an algorithm for the concealment of pictures using Cryptography and Steganography. The algorithm is to encrypt a photo in jpg format using a variant of Vigenere encryption before being hidden in another photograph of the same format._x000D_ The idea came from the problem that some users of mobile devices versus subtraction techniques using hacking information or for loss or theft of the device, because if these photos contain users who wish to maintain confidence in their devices, to be subtracted from somehow subtracted who can use so that aggrieve the owner of the photographs_x000D_ The proposal seeks to achieve total concealment picture without losing the quality of the original image nor the will to hide it, so that is undetectable by any person with access to the device. Only those who have made use of the algorithm can tell what it actually contains